Copyright Protection Of The Song "Akad" Created By “Payung Teduh” In Case Covered By Hanin Dhiya Based On Copyright Law - Damaris Eka Wijaya; Hasto Sasmito; Gunarto Gunarto (Jurnal Akta, 2018)
Technology is in progress increasingly sophisticated, enables everyone to explore and showcase her work in a variety of ways, one of which is now very easy to find is to upload video footage in a private channel on the YouTube site. However, disputes arise when recording on the channel associated with copyright issues. One of them is the activity of singing songs of others. The problems discussed in this study is how the Top Tracks Copyright Protection “Akad” Created by Payung Teduh In Case Cover Version By Hanin Dhiya Seen From the Copyright Act. The research approach is Normative legislation reviewing Act No. 28 of 2014 on Copyright. The results of this study explains that the song “Akad” is the creation of Payung Teduh, and copyright is protected by the Copyright Act, in order to perform a cover of the song, so it needed permission from Payung Teduh, as a tribute to the work of someone else's copyright. If this right is violated, the creator has the right to prosecute the song cover both civil and criminal.Keywords : Protection Law, Copyright, Cover Songs.